IMF and third - World political instability - Sidell, Scott R. (London, 1988)
Not since Cheryl Payer launched her attack on the IMF in 1975 has anyone set out to examine systematically whether IMF supported economic austerity programmes actually promote or exacerbate political instability in Third World nations. In an attempt to address one of the most critical questions facing the global debt crisis, Dr Sidell ambitiously sets out to examine nearly 100 nations around the world during the years 1969-77 to determine whether the IMF does indeed encourage politically destabilising activities through the austere policies which it supports. Dr Sidell's approach draws on work from a number of disciplines in the behavioural sciences, exploring such findings within the context of a rigorous statistical analysis of data from nearly 900 total cases. The conclusions revealed by Dr Sidell will undoubtedly influence the direction and legitimacy of the policies supported by the IMF and other international financial institutions.
Keywords: International monetary fund